2015
DOI: 10.1371/journal.pone.0129654
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Supramaximal Cycle Exercise on Plasma FFA Concentration in Obese Adolescent Boys

Abstract: AimsThe aims of the present study are 1) to evaluate the free fatty acid (FFA) profile and 2) to determine the relative anaerobic and aerobic contributions to total energy consumption during repeated supramaximal cycling bouts (SCE) in adolescent boys with different body weight statuses.Materials and MethodsNormal-weight (NW), overweight (OW), and obese (OB) adolescent boys (n =15 per group) completed a SCE sessions consisted of 6 x 6s maximal sprints with 2 min of passive rest between each repetition. Plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“… 11 In a recent study, Racil et al 11 on an outdoor athletics track reported that HIT (15 s) at 100% of maximal aerobic speed (MAS) induced better results in body composition and in the rate of perceived exertion at maximal effort in obese female adolescents, compared with training at moderate intensity (80% of MAS). In addition, Jabbour et al 12 evaluated the acute effect of a new form of exercise (very brief—6 s), which has been shown to be tolerable for experimental subjects and was indeed able to enhance LO. More other studies have also shown that HIT improved insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“… 11 In a recent study, Racil et al 11 on an outdoor athletics track reported that HIT (15 s) at 100% of maximal aerobic speed (MAS) induced better results in body composition and in the rate of perceived exertion at maximal effort in obese female adolescents, compared with training at moderate intensity (80% of MAS). In addition, Jabbour et al 12 evaluated the acute effect of a new form of exercise (very brief—6 s), which has been shown to be tolerable for experimental subjects and was indeed able to enhance LO. More other studies have also shown that HIT improved insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although most researchers agree that this intervention is extremely beneficial in individuals with excess body weight,10 this protocol is extremely difficult, as participants must tolerate considerable discomfort. Given that very brief high-intensity exercise in the form of sprint, which typically lasts 6–10 s, induces substantial improvements in performance and health-related outcomes,9 the present training model was remarkably short in duration and was tolerated extremely well by our experimental participants as previously shown by Jabbour et al 17…”
Section: Training Sessionmentioning
confidence: 55%
“…The optimal load corresponded to the load at which maximal power (PO max ) was achieved. As previously developed by our laboratory17 this load was then used for the training protocol that followed. The force-velocity test was also performed every 2 weeks to adjust the individual power level of the HIT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same training protocol has been previously developed and tested by our laboratory (Jabbour and Iancu ; Jabbour et al. ). Each of the prescribed sessions began with a 5 min warm‐up consisting of continuous cycling at moderate intensity corresponding to 40–50% of each participant's HRmax, and was followed by six repetitions of SCE intervals with 2 min of passive recovery between each repetition.…”
Section: Methodsmentioning
confidence: 99%